1991
DOI: 10.1080/00223980.1991.10543322
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Sexual Abuse: Family-of-Origin and Family-of-Procreation Characteristics of Female Adult Victims

Abstract: We examined connections between incest victims' family-of-origin and family-of-procreation characteristics in a sample of 40 American women who were in treatment for childhood or adolescent experiences of victimization. Retrospective data on their families-of-origin were collected along with their perceptions of current relationships with family members in the three-generational system. Results showed a close association between family-of-origin and family-of-procreation characteristics, especially in the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…Of these articles, one discussed the prevalence of incest in the lives of abusive mothers (Goodwin, McCarty, & DiVasto, 1982), and the remainder focused on difficulties experienced by this population including problems with setting limits, feelings of being overwhelmed (Gelinas, 1983); ambivalence about the parenting role, emotional estrangement between mothers and daughters, role-reversal, and blurred boundaries (Burkett, 1991); and differences in confidence and emotional control in abused versus control participants (Cole & Woolger, 1989;Cole, Woolger, Power, & Smith, 1992). Finally, Carson, Gertz, Donaldson, and Wonderlich (1991) suggested from their study that family-of-origin characteristics, particularly issues of intimacy, individuation, and autonomy, filter down to the family of procreation. Clinical observations and case reports of relational difficulties of mothers who report incest are well documented.…”
mentioning
confidence: 99%
“…Of these articles, one discussed the prevalence of incest in the lives of abusive mothers (Goodwin, McCarty, & DiVasto, 1982), and the remainder focused on difficulties experienced by this population including problems with setting limits, feelings of being overwhelmed (Gelinas, 1983); ambivalence about the parenting role, emotional estrangement between mothers and daughters, role-reversal, and blurred boundaries (Burkett, 1991); and differences in confidence and emotional control in abused versus control participants (Cole & Woolger, 1989;Cole, Woolger, Power, & Smith, 1992). Finally, Carson, Gertz, Donaldson, and Wonderlich (1991) suggested from their study that family-of-origin characteristics, particularly issues of intimacy, individuation, and autonomy, filter down to the family of procreation. Clinical observations and case reports of relational difficulties of mothers who report incest are well documented.…”
mentioning
confidence: 99%
“…Consistent across the literature have been reports that adult women who were sexually victimized as children exhibit a variety of difficulties in relationship to self and in relationship to others (Carson, Council, & Volk, 1989;Carson, Gertz, Donaldson, & Wonderlich, 1990;Cole & Putnam, 1992;Dinsmore, 1991;Downs, 1993;Finkelhor, 1986;Harter, Alexander, & Neimeyer, 1988;Tsai & Wagner, 1979). In terms of relationship difficulties with self, Cole and Putnam (1992) suggested that the incestuous experience results in a disruption of self-development which creates deviations in the integration, definition, and regulation of different aspects of the self.…”
Section: Introductionmentioning
confidence: 88%
“…La transmission intergénérationnelle de l'abus sexuel intrafamilial est un thème fréquemment abordé dans les discussions cliniques. En fait, la présence d'abus sexuels au sein de la famille d'origine est souvent considérée comme un facteur de risque important (Barrett, Sykes et Byrnes, 1986 ;Carson et al, 1991). Toutefois, il n'existe pas, à notre connaissance, de recherches empiriques sur la prévalence de ce phénomène.…”
Section: Structures Et Modes D'organisation Des Relations Familialesunclassified
“…En premier lieu, plusieurs chercheurs constatent la présence de frontières intergénérationnelles floues entre les systèmes familiaux d'origine des parents et le système familial des individus où l'abus sexuel se déroule (Carson et al, 1991). Cette caractéristique constitue d'ailleurs une condition probablement préalable, voire essentielle, à la transmission intergénérationnelle de l'abus sexuel.…”
Section: Structures Et Modes D'organisation Des Relations Familialesunclassified
See 1 more Smart Citation